How Migrant Networks Facilitate Trade: Evidence from Swiss Exports - Pierre-Louis Vézina (Swiss Journal of Economics and Statistics, 2012)
This paper uses Swiss data and two novel instrumental variables to test the channels through which migrants promote trade. Using immigration in France and visa restrictions as instruments for immigrantion in Switzerland, I identify a protrade effect that takes place entirely on the extensive margin, i.e. on the number of products rather than the value of exports. This suggests networks reduce beachhead costs. I also find that migrants networks can substitute for institutions but only when products are differentiated. This suggests that differentiated products are trust-intensive or that migrants substitute for institutions by providing information rather than trust.
Keywords: F22; F14; D73; D8; 330; trade; migration; corruption